Process Optimization and Antioxidant Activity of Pine Needle Essential Oil Extracted by Microwave-assisted Extraction - Suyuan LÜ; Bingqing SHANG; Luyan SUN; Guolong LIU; Fa ZHAO; Xiuqing LIANG; Qiu WU; Yue GENG (Shipin gongye ke-ji)
Objective: To optimize the best process for the extraction of pine needle essential oil from Pinus tabuliformis, and to conduct its compositional analysis and antioxidant capacity. Methods: Response surface methodology was used to optimize the process of extracting the pine needle essential oil from Pinus tabuliformis by microwave-assisted extraction (MAE), the components of essential oil were identified by gas chromatography-mass spectrometry (GC-MS) and the antioxidant activity was verified by DPPH and ABTS+ free radicals scavenging ability as indicators. Results: The optimal extraction processes were as follows: extraction time 55 min, microwave power 550 W, liquid-to-solid ratio 10:1 mL/g, the predicted yield was 0.245%, and the validation result of the optimized process was 0.238%. A total of 104 candidate components were obtained from the essential oil, with major components including thunbergol (3.938%), and verticillol (3.597%), and so on. In the antioxidant experiment, L-ascorbic acid was used as a control to determine the DPPH and ABTS+ free radicals scavenging ability, and the half maximal inhibitory concentration (IC50) was 101.74 and 12.39 mg/mL, respectively. Meanwhile, at the concentration of essential oil of 128.00 mg/mL, the DPPH free radical scavenging rate could reach 64.92% and the ABTS+ free radical scavenging rate could reach 84.11%. Conclusion: By optimizing the microwave-assisted extraction process of pine needle essential oil from Pinus tabuliformis, and measuring the main volatile components of pine needle essential oil obtained by this method, its antioxidant activity was confirmed, which would provide theoretical support for the development of green and efficient extraction methods of pine needle essential oil and further utilization of pine needle essential oil resources.